Effect of dark sweet cherry powder consumption on the gut microbiota, short-chain fatty acids, and biomarkers of gut health in obese db/db mice - García Mazcorro, José Francisco; Lage, Nara N.; Mertens Talcott, Susanne U.; Talcott, Stephen; Chew, Boon; Dowd, Scot E.; Kawas Garza, Jorge Ramsy; Noratto, Giuliana D. (2018)
ABSTRACT Cherriesarefruitscontainingfiberandbioactivecompounds(e.g.,polyphenolics)with the potential of helping patients with diabetes and weight disorders, a phenomenon likely related to changes in the complex host-microbiota milieu. The objective of this study was to investigate the effect of cherry supplementation on the gut bacterial composition,concentrationsofcaecalshort-chainfattyacids(SCFAs)andbiomarkers ofguthealthusinganinvivomodelofobesity.Obesediabetic(db/db)micereceiveda supplementeddietwith10%cherrypowder(supplementedmice,n=12)for12weeks; obese (n=10) and lean (n=10) mice served as controls and received a standard diet without cherry. High-throughput sequencing of the 16S rRNA gene and quantitative real-timePCR(qPCR)wereusedtoanalyzethegutmicrobiota;SCFAsandbiomarkers of gut health were also measured using standard techniques. According to 16S sequencing, supplemented mice harbored a distinct colonic microbiota characterized by a higher abundance of mucin-degraders (i.e., Akkermansia) and fiber-degraders (theS24-7family)aswellaslowerabundancesofLactobacillusandEnterobacteriaceae. Overall this particular cherry-associated colonic microbiota did not resemble the microbiotainobeseorleancontrolsbasedontheanalysisofweightedandunweighted UniFracdistancemetrics.qPCRconfirmedsomeoftheresultsobservedinsequencing, thussupportingthenotionthatcherrysupplementationcanchangethecolonicmicrobiota.Moreover,theSCFAsdetectedinsupplementedmice(caproate,methylbutyrate, propionate, acetate and valerate) exceeded those concentrations detected in obese and lean controls except for butyrate. Despite the changes in microbial composition and SCFAs, most of the assessed biomarkers of inflammation, oxidative stress, and intestinal health in colon tissues and mucosal cells were similar in all obese mice with and without supplementation. This paper shows that dietary supplementation with cherry powder for 12 weeks affects the microbiota and the concentrations of SCFAs in the lower intestinal tract of obese db/db diabetic mice. These effects occurred in absence of differences in most biomarkers of inflammation and other parameters of guthealth.Ourstudypromptsmoreresearchintothepotentialclinicalimplicationsof cherry consumption as a dietary supplement in diabetic and obese human patients.